Nonlinear frequency-sweep correction of tunable electromagnetic sources - Minissale, Marco; Zanon-Willette, Thomas; Prokhorov, Ivan; Elandaloussi, Hadj; Janssen, Christof (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
Tunable electromagnetic (EM) sources, such as voltage-controlled oscillators, micro-electromechanical systems, or diode lasers are often required to be linear during frequencysweep modulation. In many cases, it might also be sufficient that the degree of the nonlinearity can be well controlled. Without further efforts, these conditions are rarely achieved using free-running sources. Based on a predistortion voltage ramp, we develop in this paper a simple and universal method that minimizes the nonlinear frequency response of tunable EM sources. Using a current-driven quantum cascade laser as an example, we demonstrate that the nonlinearity can easily be reduced by a factor of ten when using a single distortion parameter γ. In the investigation of the IR absorption spectrum of ozone at 10 μm, an even better reduction of the frequencyscale error by two orders of magnitude is obtained by using the predistortion method to generate an essentially purely quadratic sweep frequency dependence that can be inverted easily to retrieve precise molecular line positions. After having tested our method on a variety of EM sources, we anticipate a wide range of applications in a variety of fields.